THE CONVERSION OF MITRA DHUAFA COOPERATIVE OF BIREUEN DISTRICT INTO SHARIAH SCHEME: An analysis of Indonesia legal norm and Fiqh Muamalah - Muhammad Abrar; Arifin Abdullah; Muslim (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The Aceh government requires all financial institutions to operate based on sharia principles, in its implementation there are still obstacles in the conversion process, such as the Mitra Dhuafa Cooperative in Bireuen Regency. The problem is that sharia principles have not been fully implemented in service products and the separation of capital made by cooperatives from conventional ones which still contain usury. The question in this study is how the implementation of Sharia principles in the Mitra Dhuafa cooperative and what are the obstacles faced in the conversion process. This research uses descriptive analysis method to describe systematically, factually, and accurately about the implementation of sharia conversion in Mitra Dhuafa Cooperative. The approach used is a case study with a qualitative research type. Research data were obtained from primary and secondary sources through literature study and interviews with related parties. Data analysis is carried out by systematically compiling information obtained from interviews, field notes, and other documents so that it can be understood and interpreted properly. The results showed that although Mitra Dhuafa Cooperative has converted to a sharia system, there are still some things that are not fully in accordance with sharia principles, especially in the management of capital and sources of funds and product services that are not fully sharia principles. In the perspective of fiqh muamalah, the management of initial funds after converting to sharia must be clean from the elements of usury and gharar, it is also important for cooperatives to provide education to members to understand how the Islamic banking system. It needs support from various cross-sectors to evaluate the constraints and challenges faced by financial institutions after being converted to sharia.